Transient Serous Retinal Detachment Possibly Related to Strenuous Exercise. (September 2017) - Anderson, Matthew Frederick; Fielden, Michael; Ells, Anna
Purpose: To report a case of transient serous retinal detachment, which may have been caused by hypertensive choroidopathy associated with exercise. Methods: Case report with optical coherence tomography and fundus fluorescein angiography imaging. Results: A 26-year-old woman noticed loss of vision in her left eye following sprinting maximally on a treadmill. Her left vision reduced to Counting Fingers, and she had a serous retinal detachment involving the left macula and inferior fundus. Optical coherence tomography confirmed a serous retinal detachment. Fluorescein angiography showed multilobular pooling of dye in the subretinal space. One week later, her vision had improved spontaneously to 20/25, and the detachment had resolved. Results of her uveitis workup were normal. Conclusions: In the absence of other plausible etiologies, we suggest that the rapidly, spontaneously resolving detachment may have been due to hypertensive choroidopathy, secondary to marked elevation in her blood pressure during maximal exercise.